Legacy and novel brominated flame retardants in indoor dust from Beijing, China: Occurrence, human exposure assessment and evidence for PBDEs replacement - Wang, Jiandi; Wang, Yuwei; Shi, Zhixiong; Zhou, Xianqing; Sun, Zhiwei (The Science of the total environment, 2018)
Levels of legacy brominated flame retardants (BFRs), including tetrabromobisphenol A (TBBPA), hexabromocyclododecane isomers (HBCDs) and polybrominated diphenyl ethers (PBDEs), and six currently used novel BFRs were determined in house dust and office dust collected from a community in Beijing, China. This is the first study where the three kinds of legacy BFRs and novel BFRs were all measured in dust samples from China. HPLC-MS/MS was used for the detection of TBBPA and HBCDs, and the other BFRs were tested on a GC-NCI/MS. Decabromodiphenyl ethane (DBDPE), PBDEs, HBCD and TBBPA were found to be the main BFRs in the dust samples, with median levels of 709, 241, 199 and 26.7ng/g dust, respectively. Due to the high density of electronic equipment used in offices, levels of BFRs in office dust were found to be higher than those in house dust. DBDPE, as a replacement of PBDEs, was the predominant BFR, and the median level of DBDPE was not only several orders of magnitude higher than that of other novel BFRs but also 3 to 27 times higher than that of the three legacy BFRs, indicating that the consumption pattern of BFRs in the Chinese market has shifted from PBDEs to PBDE alternatives. Median estimated daily intakes (EDIs) of BFRs through dust ingestion for adults (>20years) and toddlers (<2years) were in the range of 2.8×10−5–0.201ng/kg body weight (bw)/day and 5.7×10−4–2.52ng/kg bw/day, respectively. The body burden of BFRs for toddlers was far higher than that for adults; however, a comparison between EDIs and threshold values suggested that daily intakes of BFRs for both adults and toddlers were unlikely to raise significant health concerns. [Display omitted] •BFRs were measured in house dust and office dust collected from Beijing, China.•Levels of DBDPE were higher than those of any other BFRs in this study.•The consumption pattern of BFRs in China may have shifted from PBDEs to non-PBDE BFRs.•The daily intake of BFRs is unlikely to raise significant health concerns.